2015
DOI: 10.1016/j.neulet.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic activator of Nurr1 induces dopaminergic gene expression and protects against 6-hydroxydopamine neurotoxicity in vitro

Abstract: Degeneration of dopaminergic neurons in Parkinson’s disease (PD) is associated with decreased expression of the orphan nuclear receptor Nurr1 (NR4A2), which is critical for both homeostasis and development of dopamine (DA) neurons. The synthetic, phytochemical-based compound, 1,1-bis (3′-indolyl)-1-(p-chlorophenyl) methane (C-DIM12) activates Nurr1 in cancer cells and prevents loss of dopaminergic neurons in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of PD in mice. In the present study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…After a comparative analysis, C-DIM12 (higher affinity for Nurr1) has the most potent neuroprotective activity and anti-inflammatory effect in MPTP-lesioned rat model of PD [53]. It could enhance the expressions of Nurr1 and Nurr1-regulated proteins such as TH and DAT, and Nurr1-mediated recruitment of CoREST and the NF-κB-mediated inflammatory genes expression are suppressed in SN [5355]. …”
Section: Nurr1-activating Compoundsmentioning
confidence: 99%
“…After a comparative analysis, C-DIM12 (higher affinity for Nurr1) has the most potent neuroprotective activity and anti-inflammatory effect in MPTP-lesioned rat model of PD [53]. It could enhance the expressions of Nurr1 and Nurr1-regulated proteins such as TH and DAT, and Nurr1-mediated recruitment of CoREST and the NF-κB-mediated inflammatory genes expression are suppressed in SN [5355]. …”
Section: Nurr1-activating Compoundsmentioning
confidence: 99%
“…Because of their dopaminergic properties [1], rat dopaminergic N27 cells have been widely used in in vitro models for PD studies [1,3]. They have also been used in studies seeking to understand problems such as neurotoxicity, oxidative stress, and histone deacetylase (HDAC) and other molecular pathways [4][5][6]. While there have been studies on synaptophysin signaling in N27 cells, the electrophysiological effects of graphene on N27 cells are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nurr1 activation has been shown to confer neuroprotection ( Barneda-Zahonero et al, 2012;Hammond and Safe, 2015;Hammond et al, 2018) and is anti-inflammatory through its ability to suppress nuclear factor kappaB (NFκB) activation (Saijo et al, 2009;De Miranda et al, 2015), yet there are no reports on whether Nurr1 induction is neuroprotective in models of ischemic stroke. Ischemia induced Nurr1 mRNA upregulation has been reported in global ischemia in gerbils (Honkaniemi and Sharp, 1996) and in rats with permanent middle cerebral artery occlusion (Honkaniemi et al, 1997), whereas protein levels of Nurr1 were shown to be decreased in mice subjected to transient ischemia (Erdö et al, 2004).…”
Section: Introductionmentioning
confidence: 99%